Praying with Blathmac Martyrdom and memory in early Irish devotional practice - Bergholm, Alexandra (2022)
The mid-eighth-century Old Irish text known as the poems of Blathmac is a long devotional composition meditating on the mystery of Christ’s cross and its significance for salvation history. Since the discovery and subsequent publication of the text nearly six decades ago, the work has garnered considerable scholarly interest for its linguistic and socio-historical value, but many aspects of its devotional orientation remain less systematically explored. This article examines the poems’ devotional discourse by focusing on the intersections of martyrdom and memory in Blathmac’s composition. Taking as a starting point the text’s intended use as a prayer, the discussion considers how the text’s overarching interest in exemplary acts of self-sacrifice relates to the practices of ritual commemoration, and how these strategies of collective memory work to convey and sustain a shared understanding of Christian identity.
Keywords: Old Irish religion; Prayer; Ritualization; Rituals